Web-Based Expert System for Optimizing of Traffic Road in Developing Countries - B. Z. Alshetwi, Abduraouf.; Atiq Abdullah O.K. Rahmat, Riza; Nazri Borhan, Muhamad; Ismael Albrka Ali, Shaban; Imhimmed Mohamed Irtema, Hamza; Y. Y. Alfakhria, Aboubaker (International Journal of Engineering and Technology, 2018)
In current times, the increase of road users using road traffic include street carriers, vehicles, pedestrians, buses and other forms of transportation, both individually or in combination, utilizing the universal means to travel. Vehicle regulation and laws governing traffic are traffic laws, whereas road rules are natural regulation and standards that might be advanced in time in facilitating the traffic flow to be methodical and well-timed in emerging countries.Â  Experts of the traffic road system [TRSys] suggests a procedure for road traffic experts and offers supervision and ice advertising on selecting effective and suitable policies. The road traffic development in dealing with traffic-associated complications needs various wide-ranging knowledge and information achievable from road traffic sources for example written sources [books, manuals, technical reports and standards] and traffic expert opinions. A computer tool is utilized in developing the expert system is Web-based expert system Microsoft [PHP]. It is a dominant application containing all the essential services to construct a Windows or Web-based applications for instance expert systems quick and proficient tools. TRSys is an online consultant system in traffic safety to implement a road network in developing countries that can help engineers, consultants, contractors, civil engineering students, and decision makers. The usefulness of the expert system [TRSys] to give recommendations which are appropriate to Road Network for Developing Countries. Traffic Road System [TRSys] is an innovative system advanced in this research to aid junior engineers. It also helps decision-makers and students in identifying traffic complications in developing countries and consequently recommend the application of suitable solutions.Â Â